Towards a climate-health approach in Indian healthcare: Perspectives of specialist doctors on health impacts of extreme heat in Hyderabad - Sai Venkata Sarath Chandra N; Aalok Khandekar; Anant Maringanti (The Journal of Climate Change and Health, 2023)
Introduction: Climate change impacts human health by exacerbating existing vulnerabilities to communicable and non-communicable diseases and creating new ones. Consequently, there has been increasing recognition of the need for a dedicated focus on ‘climate health’ in medical education and the healthcare profession globally. In this study, we explored the perspectives of doctors on the impact of heat on human health in Hyderabad, India and how a climate health approach can be adopted across Indian healthcare. Methods: A global literature review on climate health broadly, and heat health specifically was carried out. Based on our analysis of the literature, we developed an interview questionnaire and conducted semi-structured interviews with 16 specialist physicians in order to understand their perspectives on the impacts of heat on human health in the region of Hyderabad and institutional transformations necessary to better address questions of heat health. Interview findings were interpreted against extant research on climate health. Results: Climate health and heat-health challenges are aggravating globally, and the doctors perceive that the Hyderabad region is no exception. While efforts are underway to operationalize a climate health approach in healthcare systems in countries of the Global North, such an orientation is almost absent from the context of Indian medical education and healthcare. Conclusion: Impacts of climate change and heat on human health are becoming more apparent in the Hyderabad region. This suggests a strong need to incorporate greater attention to climate health and heat health as part of medical education and the healthcare system in India. Funding: This research has been conducted as part of the “Cool Infrastructures: Life with Heat in the Offgrid City” project funded by the Economic and Social Research Council (ESRC), UK (Award No: ES/T008091/1).